Optimizing BAZNAS Village Microfinance Financing Efforts to Improve the Welfare of Business Partners - M. Nanang Febrianto; Ahmad Fauzi Asshidqi; Lisa Yuni Lestari; Zulfah Jannatul Karimah; Irtifa Umi Azizah; Johan Dwi Sutikno; Binti Nur Asiyah (Indonesian Journal of Community Engagement, 2026)
Islamic Social Finance plays a crucial role in improving the welfare of the community. The role of Baznas Microfinance Village (BMD) is considered a solution and alternative capital financing for MSMEs emphasizing sharia principles. Therefore, this community service aims to optimize Baznas Microfinance Village financing to improve the welfare of mustahik. The design of community service is through the Economic Empowerment Model with assistance in increasing partner capacity, while this service is carried out through qualitative field research to partners who are members of Baznas Microfinance Village (BMD) in Tulungagung. Field findings show that most of the business partners who submitted are fast food culinary businesses dominated by women with the aim of financing capital for the purchase of equipment and business needs. Business capacity building is carried out by regularly monitoring capital use, facilitating halal certification, creating NIBs, and curating MSME products as well as digital marketing training through marketing through social media and creating banner designs, logos, Qris, Maps. In addition, business partners are involved in activities such as bazaars as a form of cross-sector collaboration in local government activities. The existence of partner capital financing not only obtains business capital but also increases the independence and skills of partners. Thus, the primary impact felt by business partners is increased productivity, in terms of turnover, competitiveness, and welfare. Collaboration across sectors, stakeholders, and policymakers can encourage optimal financing and sustainability for MSMEs.